The odyssey of Ibn Battuta uncommon tales of a medieval adventurer - Waines, David (The University of Chicago Press, 2010)
Ibn Battuta was, without doubt, one of the world's truly great travelers. Born in fourteenth-century Morocco, and a contemporary of Marco Polo, Ibn Battuta left an account in his own words of his remarkable journeys, punctuated by adventure and peril, throughout the Islamic world and beyond. Whether sojourning in Delhi and the Maldives, wandering through the mazy streets of Cairo and Damascus, or contesting with pirates and shipwreck, the indefatigable Ibn Battuta brought to vivid life a medieval world brimming with marvel and mystery. Carefully observing the great diversity of civilizations that he encountered, Ibn Battuta exhibited an omnivorous interest in such matters as food and drink; religious differences among Christians, Hindus, and Shia Muslims; and ideas about purity and impurity, disease, women, and sex.